(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: Present study was undertaken to find out the long term effect of application of compression probe after haemorrhoidectomy in the treatment of bleeding haemorrhoids. Materials and methods: They study was carried out in the Department of Clinical Surgery, Russian People’s Friendship University, Moscow, Russia, from January 1992 to December 2001, on 80 patients, equally divided into two groups, case (haemorrhoidectomy plus application of compression probe) and control (haemorrhoidectomy only). Results: Long term follow up showed higher good outcome in case group (82.1%) compared to control (53.8%) (P<0.05), satisfactory and unsatisfactory outcome was higher in control group (17.9% and 28.2%) compared to case group (12.8% and 5.1%). Conclusion: Application of compression problem after haemorrhoidectomy in patients with bleeding haemorrhoids gives better long term results. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 129-132 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14939